2014
DOI: 10.1016/j.ydbio.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cochleovestibular nerve development is integrated with migratory neural crest cells

Abstract: The cochleovestibular (CV) nerve, which connects the inner ear to the brain, is the nerve that enables the senses of hearing and balance. The aim of this study was to document the morphological development of the mouse CV nerve with respect to the two embryonic cells types that produce it, specifically, the otic vesicle-derived progenitors that give rise to neurons, and the neural crest cell (NCC) progenitors that give rise to glia. Otic tissues of mouse embryos carrying NCC lineage reporter transgenes were wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 64 publications
7
61
0
Order By: Relevance
“…However, our data on melanocyte migration toward their target location in the cochlea, which to our knowledge has not been shown before in such clarity, suggests that cochlear melanocytes in humans migrate through the periotic mesenchyme from the opposite side. In agreement, several studies in mice embryos show the presence of neural crest derivatives or melanocytes near this part of the otic vesicle around embryonic day 10.5 (Steel et al, 1992; Freyer et al, 2011; Adameyko et al, 2012; Wakaoka et al, 2013; Sandell et al, 2014). Therefore, although the peripheral glial cells in the cochlea originate from the migratory wave of neural crest cells from rhombomere 4, we now hypothesize that cochlear melanocytes originate from a different wave of neural crest cells, namely those delaminating from the region at rhombomere 6, at the location of the developing glossopharyngeal nerve (cranial nerve IX) and the third pharyngeal arch.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, our data on melanocyte migration toward their target location in the cochlea, which to our knowledge has not been shown before in such clarity, suggests that cochlear melanocytes in humans migrate through the periotic mesenchyme from the opposite side. In agreement, several studies in mice embryos show the presence of neural crest derivatives or melanocytes near this part of the otic vesicle around embryonic day 10.5 (Steel et al, 1992; Freyer et al, 2011; Adameyko et al, 2012; Wakaoka et al, 2013; Sandell et al, 2014). Therefore, although the peripheral glial cells in the cochlea originate from the migratory wave of neural crest cells from rhombomere 4, we now hypothesize that cochlear melanocytes originate from a different wave of neural crest cells, namely those delaminating from the region at rhombomere 6, at the location of the developing glossopharyngeal nerve (cranial nerve IX) and the third pharyngeal arch.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, it has been reported that cranial melanocytes can arise from Schwann cell precursors migrating together with outgrowing nerves (Adameyko et al, 2009; Adameyko et al, 2012). As Schwann cell precursors arrive in the cochlea via the cochlear nerve (Sandell et al, 2014), it is tempting to propose that melanocytes (precursors) may travel along the same path. However, our data on melanocyte migration toward their target location in the cochlea, which to our knowledge has not been shown before in such clarity, suggests that cochlear melanocytes in humans migrate through the periotic mesenchyme from the opposite side.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with delamination of neuroblasts, glial cells also migrate from the neural crest [25, 26] and serve as supporting cells for PANs. Myelinating Schwann cells, a glial subtype, surround the peripheral process of type I PANs and non-myelinating Schwann cells surround the peripheral processes of type II PANs.…”
Section: Introductionmentioning
confidence: 99%
“…A similar intermingling of placode and neural crest-derived neurons has been suggested for the lateral line and the inner ear [Freyer et al 2011], with a report of variable numbers of neurons from the spiral ganglion and vestibular neurons as well as hair cells being derived from Pax3-expressing neural crest precursors [Freyer et al 2011]. However, in a different transgenic mouse line expressing Pax3-cre, transgene expression labeled only Schwann cell precursors that tightly interacted with the developing vestibular and cochlear ganglion neurons [Sandell et al 2014]. Thus, the neural crest contribution to the inner ear and lateral line systems does not appear to include the neuronal lineage [Mao et al 2014].…”
Section: Evolution and Development Of Peripheral Sensory Structures Amentioning
confidence: 99%